Life History Patterns of the Bornean Earless Monitor, Lanthanotus borneensis (Reptilia: Squamata: Lanthanotidae) - Veronica, Leah (Veronica Leah, 2024)
The Bornean Earless Monitor, Lanthanotus borneensis, the monotypic living representative of the family Lanthanotidae and an endemic of Borneo, has been the topic of intense interest by researchers, conservationists and the general public in the past decade. The threat upon this species resulting from illegal poaching and exotic pet trade has augmented the stress amongst herpetologists to document the life history patterns of L. borneensis. However, due to its cryptic morphology and sedentary lifestyle, in addition to rarity in the wild, few field observations have been made. This research focuses on quantifying habitat use and associated environmental factors in shaping the distribution of the species at two localities in the interior of Sarawak State, East Malaysia. A real-time use of radio telemetry was employed to estimate microhabitat utilisation, movement and thermal biology of the two populations of the Bornean Earless Monitor. In addition, the ethnoherpetological significance of the target species was evaluated. The species is found to be a stream obligate, restricted within riparian and other aquatic zones. A total of six microhabitat types were associated: (i) rocks underwater (61.73%), (ii) within fissures of exposed bedrocks (23.5%), (iii) isolated shallow pools (5.6%), (iv) rocks on dry streambanks (4.32%), (v) under fallen logs (2.5%) and (vi) underground in loose soil (2.47%). Ambient temperature, canopy cover and stream width are demonstrated to be significant environmental predictors. Females were observed to occupy more microhabitats compared to males, and submerged rocks were the main microhabitats selected. Movement is restricted within stream regions, and a slight overlap of space use between sexes was recorded. Using 100% minimum convex polygons, mean home range sizes is 500.83 ± 300.89 m2. There was no significant difference in home range sizes between the sexes or within size classes. This research has also tested for possible effects of lunar phase on lizard movement but found no significant relationship. L. borneensis is shown to be a thermoconformer, mean body temperature 25.6°C (22.8–28.0°C ± 0.08 SE, n = 120) and no significant difference was found between the sexes. Ambient temperature was strongly correlated to body temperature and more strongly, between substrate temperature and body temperatures, supporting thigmothermy as the main method of thermoregulation. Incidental observations of this species were collected to increase knowledge on the natural history of the species. This includes notes on diet and defensive strategies of this species. Opportunistic observations were made of L. borneensis preying upon a small species of crab (Borneosa kapit), and a single faecal sample showed evidence of predation on a species of cockroach of the family Blaberidae. Regarding defensive strategies, it was observed that the study species exhibited five strategies which are: i. Body contortion in refugia, claws used to cling to substrate to prevent extraction; ii. ‘Death roll’; iii. Flattening of body; iv. Faecal excretion; and v. Escape. Interview surveys were conducted to collect ethnozoological data. The documentation of such knowledge suggests the cultural significance of the target species for the Iban population of central Sarawak. The ecological information collected in this study has provided valuable insight into the aspects of natural history of L. borneensis, a tropical ectotherm threatened by present anthropogenic activities such as habitat degradation and exotic pet trade. Such information can be preserved within local knowledge and will also prove useful for the conservation and management of similarly threatened species in Borneo.